Subgroup detection-based dental caries status and inequalities trend exploration: A nationwide, 10-year-repeated cross-sectional study - He, Jie; Liang, Hongyuan; Kang, Jian; Yuan, Chao (Frontiers in Public Health, 2022)
Background The goal of this study was to identify potentially important factors for the dental health though heterogeneous effects of risk factors within Chinese adolescent populations with different characteristics by analyzing the repeated cross-sectional data collected in the 3rd (2005) and 4th (2015) National Oral Health Survey. Methods We studied the relationships between the decayed, missing and filled permanent teeth (DMFT) score, which was a discrete value, with the caries risk factors (region, census type, gender, only child or not, parents' education level, tooth bushing, dentist visit history, knowledge score, sugar intake, and pit-and-fissure sealants status), though the Poisson mixture regression model, which could identify subgroups among the full population and estimate the heterogeneous effects of risk factors simultaneously. We performed a series of tests and trend analysis based on the model fitting results to explore the primary causes for the dental caries issue clearly and intuitively. Results A total of 39,049 teenagers aged 12 years were involved in the analysis. The Poisson mixture regression model clustered all individuals into three subgroups, where the mean values (standard deviations) of DMFT were 0.18 (0.56), 1.31 (1.49), and 2.91 (1.89), respectively. Model fitting results indicated that the heterogeneous effects of the involved risk factors were significant. In addition, we also found significant differences in the distributions and trends of DMFT within different categories of selected risk factors (region, census type, gender and dentist visiting history) from the projection analysis results. The estimated and projected proportions showed that the proportion of high caries risk population in the southwestern region increased by 31.8%, and will become even more severe as it will be the major component of high caries risk population in 2025. Conclusions We found that the trends for the developments and changes of dental caries within populations with different characteristics were inequality. The regional difference is the primary factor for diversified changes in DMFT. The findings in this study provide support for intervention and prevention policies for the deterioration of dental caries risk within different adolescent populations.